Segmentation of Moving Object in Video Surveillance using Optical Drift (International Journal of Advanced Research in Science, Management and Technology, 2017)
With the abrupt increase of motor vehicles, the advanced Intelligent Traffic Monitoring System is important in today's world. Automatic video segmentation plays an important role in the ITMS. Many algorithms have been proposed on automatic video segmentation. However, due to the large computation, many of them can-not be used for the real-time applications. Segmentation of moving objects in a scene is often desired in many applications for monitoring motion. In the project, we look at traffic videos. The approach used for object-oriented video segmentation is based on motion coherence.
Keywords: Lucas Kanade method, Motion vector Optical flow estimation, SAD ,Video segmentation.